Investigating the Manifestation of Teaching Expertise Feature among Novice and Experienced EFL Teachers - Saeed Mehrpour; Zahraossadat Mirsanjari (Journal of English Language Teaching and Learning, 2016)
The present study was an attempt to investigate the manifestation of teaching expertise of EFL teachers in Iranian formal educational context. More specifically, it was intended to study how teachers of English in Iranian high schools and General English instructors in a state university manifest features of teaching expertise. The study also compared the expertise features of novice teachers with those of experienced ones in both high schools and university. To achieve these goals, through a qualitative research, 10 high school teachers and 10 university instructors were purposively selected to be observed and interviewed. Each group consisted of 5 novice and 5 experienced teachers. After 2-3 sessions of observation (which functioned as the main source of data) and one session of interview with all participants, an attempt was made to extract cases or instances of expertise in their teaching practice. These instances were later categorized into 6 types of expertise: expertise in management, motivational expertise and providing guidance and feedback, instructional expertise, content knowledge expertise, expertise in making connections between subjects of study, and expertise in dealing with challenges. A table consisting of these expertise types and all those instances or cases of expertise (extracted from the observation reports and also the literature) was designed. The data for each teacher was analyzed closely again and those cases which were present in their teaching practice were checked in the table. The next step was to look carefully at the patterns of expertise in each group of teachers. The analysis of the collected data revealed that teaching expertise was manifested almost similarly in the teaching practice of the four groups of teachers. Three groups i.e. experienced high school teachers, and novice and experienced university instructors exhibited 100% success in at least one type of expertise, namely making connections between subjects of the study. This aspect of expertise in novice high school teachers proved to be just 60%. Experienced university instructors formed the only group who achieved perfect performance (100%) in two types of expertise, namely, content knowledge expertise and expertise in making connections between subjects of study. And novice high school teachers formed the only group who did not achieve perfect performance in any of the teaching expertise types.